The Role of Digital Technology Competency and Psychological Capital in Vocational Education Students: The Mediating Role of Entrepreneurial Self-Efficacy - Kholifah, Nur; Nurtanto, Muhammad; Mutohhari, Farid; Nuur Wachid Abdul Majid,; Moh Fawaid, (Journal of Technical Education and Training, 2024)
The importance of entrepreneurial intention (EI) in entrepreneurship education, particularly in addressing persistent challenges, demands a more intensive role from vocational education (VE) as a key institution responsible for creating new jobs. Entrepreneurial self-efficacy (ESE) is believed to be the most effective way to strengthen EI. Furthermore, digital technology competence (DTC), supported by psychological capital (PC), plays a crucial role in shaping ESE and EI. This research thoroughly examines the roles of DTC, PC, and ESE in fostering EI among VE students. Additionally, the study investigates the primary role of ESE as a mediator between DTC and PC in determining EI. This research involved 682 VE students who volunteered, meeting specific criteria relevant to the study's needs. Data collection was facilitated through a closed questionnaire using a four-point Likert scale, which was tested for validity and reliability. Structural Equation Modeling (SEM) was employed to analyze the data through path analysis and bootstrap methods. The study confirms the critical importance of ESE in fostering EI among students. It also highlights the significant roles of DTC and PC in enhancing ESE and shaping EI. These findings underscore the need for VE to focus on strengthening these aspects to address the issue of low EI, which in turn affects the creation of new jobs due to the insufficient number of VE graduates pursuing entrepreneurship.